Dividend policy and stock price volatility in an emerging market: Does ownership structure matter? - Phan Thi Kieu Hoa; Tran Nam Hoai (Cogent Economics & Finance, 2019)
This paper examines the impacts of dividend policy and ownership structure on stock price volatility in the Vietnamese market. The study also tests for the moderating effect of foreign/state ownership on the dividend policy-price volatility relation. The authors use a comprehensive panel dataset of non-financial firms listed publicly on the Ho Chi Minh Stock Exchange and Hanoi Stock Exchange over the period from 2008 to 2015. Employing a set of different econometric methods, the robust results indicate that dividend yield mitigates stock price volatility in the emerging market of Vietnam. The price-stabilising effect of foreign (and state) involvement has no longer been significant after the global financial crisis. Also, the study finds no moderating effect of ownership structure on the relation between dividend yield and price volatility during the sample period. The finding of the influence of dividend policy on stock market risk has critical implications for the investment landscape in emerging markets.
Keywords: C33; E44; G23; 330; dividend policy; ownership structure; state ownership; foreign ownership; emerging markets